Intercomparison of aerosol single‐scattering albedo derived from AERONET surface radiometers and LARGE in situ aircraft profiles during the 2011 DRAGON‐MD and DISCOVER‐AQ experiments. Issue 12 (17th June 2014) - Schafer, J. S.; Eck, T. F.; Holben, B. N.; Thornhill, K. L.; Anderson, B. E.; Sinyuk, A.; Giles, D. M.; Winstead, E. L.; Ziemba, L. D.; Beyersdorf, A. J.; Kenny, P. R.; Smirnov, A.; et al.
Abstract Single‐scattering albedo (SSA) retrievals obtained with CIMEL Sun‐sky radiometers from the Aerosol Robotic Network (AERONET) aerosol monitoring network were used to make comparisons with simultaneous in situ sampling from aircraft profiles carried out by the NASA Langley Aerosol Group Experiment (LARGE) team in the summer of 2011 during the coincident DRAGON‐MD (Distributed Regional Aerosol Gridded Observational Network‐Maryland) and DISCOVER‐AQ (Deriving Information on Surface conditions from Column and Vertically Resolved Observations Relevant to Air Quality) experiments. The single‐scattering albedos (interpolated to 550 nm) derived from AERONET measurements for aerosol optical depth (AOD) at 440 nm ≥ 0.4 (mean SSA: 0.979) were on average 0.011 lower than the values derived from the LARGE profile measurements (mean SSA: 0.99). The maximum difference observed was 0.023 with all the observed differences within the combined uncertainty for the stated SSA accuracy (0.03 for AERONET; 0.02 for LARGE). Single‐scattering albedo averages were also analyzed for lower aerosol loading conditions (AOD ≥ 0.2) and a dependence on aerosol optical depth was noted with significantly lower single‐scattering albedos observed for lower AOD in both AERONET and LARGE data sets. Various explanations for the SSA trend were explored based on other retrieval products including volume median radius and imaginary refractive index as well as column water vapor measurements. Additionally, these SSA trends with AOD were evaluated for one of the DRAGON‐MD study sites, Goddard Space Flight Center, and two other Mid‐Atlantic AERONET sites over the long‐term record dating to 1999.